2014
DOI: 10.5653/cerm.2014.41.2.68
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various assisted hatching techniques on the mouse early embryo development

Abstract: ObjectiveIn search of an ideal method of assisted hatching (AH), we compared the effects of conventional micropipette-AH and laser-AH on the blastocyst formation rate (BFR) and blastocyst cell numbers.MethodsFour- to five-week-old ICR female mice were paired with male mice after superovulation using Pregnant mare's serum gonadotropin (PMSG) and hCG. The two-cell embryos were flushed from the oviducts of female mice. The retrieved two-cell embryos underwent one of five AH procedures: single mechanical assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
4
12
0
3
Order By: Relevance
“…The rates of hatched blastocyst formation were 49.1% and 40.4% in the qLAH and qLZT-AH groups, respectively, which were significantly higher than in the groups which a smaller area of the ZP was eliminated. Their study was referenced by Park et al [ 25 ], who found a significantly higher rate of formation of hatched blastocysts after 72 hours of culture in the qLAH and qLZT-AH groups than in the control groups. In the present study, the rate of hatched blastocyst embryos was consistently the highest in the AS/qLZT-AH/V-T group ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The rates of hatched blastocyst formation were 49.1% and 40.4% in the qLAH and qLZT-AH groups, respectively, which were significantly higher than in the groups which a smaller area of the ZP was eliminated. Their study was referenced by Park et al [ 25 ], who found a significantly higher rate of formation of hatched blastocysts after 72 hours of culture in the qLAH and qLZT-AH groups than in the control groups. In the present study, the rate of hatched blastocyst embryos was consistently the highest in the AS/qLZT-AH/V-T group ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
“…Cieslak et al [ 24 ] reported that a pregnancy rate of 42.0% was obtained in a group that underwent three-dimensional partial zona dissection, using a micropipette rather than strong acid for dissecting the ZP in preimplantation genetic diagnosis and AH, which was then rotated for another round of dissection, compared to a rate of 33.3% in the control group. Additionally, Park et al [ 25 ] showed that the rate of fully hatched embryos cultivated for 72 hours after AS was 9.0% in the group in which cMAH was performed, compared to 0% in the group in which single mechanical AH. The present experiment was largely based on the report of Khalifa et al [ 26 ], who found a high incidence of hatched blastocyte embryo formation using quarter-LAH (qLAH) and qLZ-AH, which are helpful techniques for encouraging blastocysts to hatch because they eliminate the rather large area of the ZP.…”
Section: Discussionmentioning
confidence: 99%
“…Teknik ini kemudian banyak dikembangkan melalui penelitian untuk mengoptimalkan hasil, antara lain dengan cross Mechanical Assisted Hatching (cMAH). Metode yang dikembangkan oleh Park et al (2014) sebenarnya adalah pengembangan dari PZD. Namun, cMAH dikerjakan dengan membuat dua kali sayatan yang saling bersilangan.…”
Section: Metode Mekanisunclassified
“…Berbagai pengembangan metode AH menggunakan sinar laser terus dilakukan. Salah satunya adalah beberapa pengembangan penggunaan berbagai jenis sinar laser seperti 1,48 µm infrared laser diode (Park et al 2014), ZILOS-TK infrared laser optical system (Makrakis et al 2006), OCTAX laser shot system (Nishio et al 2006) dan erbium-yttriumaluminium-garnet (Er:YAG) (Obruca et al 1997).…”
Section: Laser Assisted Hatchingunclassified
See 1 more Smart Citation